Synthesis, Identification of Some New 1, 2, 4-triazole Derivatives from 2-(4-methoxyphenyl)-3-ethyl acetate -4(3H) - quinazolinone and Evaluation Anti-Oxidant Activity - Saeed, Noor Nashaat; Al-Majidi, Suaad M. H. (Iraqi Journal of Science, 2025)
In this study, novel derivatives have been synthesized for 1,2,4-triazole-quinazolinone compounds. The intermediate compound, amic acid 1, was prepared through the reaction of anthranilic acid with para-methoxybenzoyl chloride. The compound benzoxazinone 2 is prepared by reacting amic acid with acetic anhydride, which upon esterification is carried out using ethylglycinate hydrochloride. Ester derivative 3 was obtained. The first line of research involved reacting the ester derivative 3 with (semicarbazide, thiosemicarbazide, and phenylthiosemicarbazide, phenylthiosemicarbazide) respectively to give derivatives 5-8. Compounds 5-8 were cyclized in alkaline medium (2N-NaOH) gave 1, 2, 4-triazole derivatives 9-12, respectively. Alternatively, compound 4 was reacted with CS2 in an alkaline medium (20% KOH) to produce the potassium salt 13. This compound then directly reacted with aqueous hydrazine to yield compound 14. The new compositions prepared were proven using spectroscopic techniques [FT-IR, 1H-NMR, 13C-NMR,]. The last part of this research in which, these materials were tested 5, 9, 11, 12, 13, 14 for antioxidant activity using DPPH radical scavenging activity technology.